Analysis of certain biochemical indices on alloxan induced diabetic rats administered with protein isolated and purified from Vernonia amygdalina - Ihimire I.G.*, Kayode E.A. and Osagie V.E. (African Journal of Biological Sciences, 2019)
This study investigated the effect of protein isolate from leaf extract of Vernonia amygdalina in diabetic rats. Thirty (30) adults male Wistar rats were randomly divided into six (6) groups of five (5) each based on their body weight. Diabetes was induced with administration of alloxan, 150 mg/kg body weight (i.p). Group A served as the control and received 1 mL/kg body weight of 5% ethanol being solvent used, Group B received 1 mL alloxan containing 150 mg/kg only. Group C, D, E and F were respectively alloxanized but treated with 1%, 3%, 5% and 7% of protein isolate obtained from V. amygdalina leaves for 14 days. On the 15th day, the animals were humanely sacrificed and their liver homogenates were prepared. Standard biochemical procedures were adopted for determination of catalase (CAT), superoxide dismutase (SOD) activities, Malondialdehyde (MDA) and glucose levels. Data were subjected to one-way Analysis of Variance (ANOVA) with Tukey-Kramer multiple comparison post-hoc test using Graph Pad, version 6 software. Results showed that CAT activity in alloxan-induced untreated rats (1.17 μmole H2O2) was significantly (p < 0.05) lower than observed in control rats (2.10 mole H2O2). Treatment with the respective doses recorded comparable values to those observed in control rats. Similar observation was seen with SOD data. Rats treated with 7% protein isolate recorded the most significant (p < 0.05) decrease in serum glucose level. The study suggests that the protein isolate possesses anti-diabetic and hypoglycaemic effects on alloxan-induced diabetic rats.
Keywords: Protein isolates, diabetes, biochemical, hypoglycaemic, alloxanized, liver homogenate